The prevalence and risk factors of acute kidney injury in patients undergoing hip fracture surgery: a meta-analysis. Issue 1 (1st January 2021) - Li, Zi-Cai; Pu, Yan-Chuan; Wang, Jin; Wang, Hu-Lin; Zhang, Yan-Li
ABSTRACT: Acute kidney injury (AKI) was a frequent complication following hip fracture surgery, but recent studies reported inconsistent findings. Our study was aimed at clarifying the prevalence and risk factors of AKI after hip fracture surgery. Pubmed, Embase, and Web of Science were systematically searched from the inception to March 2020 to identify observational studies investigating the prevalence and risk factors of AKI in patients undergoing hip fracture surgery. Pooled prevalence and odds ratios (ORs) with 95% confidence intervals (CIs) were estimated using a random-effects model. Publication bias was evaluated with a funnel plot and statistical test. All the statistical analyses were performed using Stata version 12.0. A total of 11 studies with 16, 421 patients was included in the current meta-analysis. The pooled prevalence of AKI in patients undergoing hip fracture surgery was 17% (95%CI, 14%-21%) with substantial heterogeneity (I 2  = 95%). Postoperative serum albumin (OR 1.80; 95%CI, 1.38–2.36) was a significant predictor for AKI. Age (OR 1.01; 95%CI, 0.95–1.07) and ACE inhibitors (OR 1.38; 95%CI, 0.92–2.07) were associated with increased the risk of AKI, but the results were not statistically significant. No significant publication bias was identified through statistical tests (Egger's test, p = 0.258 and Begg's test, p = 0.087). In conclusion, our findings indicated that t he pooled AKI following hip fracture surgery was approximately 17%. Postoperative serum albumin was a potential significant risk factor for AKI. GRAPHICAL ABSTRACT: uf0001